P-408 IL-10 and IL-17 pathway enrichment in uterine fluid-derived extracellular vesicles (UF-EVs) is associated with failed implantation in women with recurrent implantation failure undergoing PGT-A. (30th June 2022) - Vanni, V.S; Giacomini, E; Scotti, G.M; Carnemolla, G; Privitera, L; Lazarevic, D; Cantone, L; Molgora, M; Delprato, D; Faulisi, S; Bollati, V; Tonon, G; et al.
Abstract: Study question: Can the UF-EVs transcriptome provide markers of implantation in women diagnosed with recurrent implantation failure (RIF)? Summary answer: Enrichment in IL-10 and IL-17 pathway transcripts in UF-EVs of women with RIF might identify those at risk for negative outcome after euploid blastocyst transfer. What is known already: Our group has recently found that transcriptomic changes occur in UF-EVs during the window of implantation and closely resemble those occurring in the endometrial tissue. Patients affected by RIF represent a debated and heterogeneous population of patients who currently undergo several investigations, empirical therapies and embryo transfer attempts, with inconclusive results. We investigated whether UF-EVs can provide markers to define subgroups of patients within the RIF population, to predict outcomes and tailor interventions. Study design, size, duration: We herein present the first sub-analysis of our previous larger observational study on the human UF-EVs transcriptome (Giacomini et al., 2021). RIF was defined by > 3 failed embryo transfers (ETs) with high quality embryos and patients affected by RIF and undergoing their first PGT-A cycle were enrolled (n = 19). Fertile women undergoing PGT-A+PGT-M for monogenic diseases and achieving successful implantation were used as controls (n = 29). PGT-A was performed by Next Generation Sequencing. Participants/materials, setting, methods: RNA-Seq was performed on UF-EVs collected on day LH + 7 of the cycle preceding that of the blastocyst transfer. Differential Gene Expression (DGE) analysis was performed between RIF patients failing implantation (Group A) versus RIF patients achieving implantation (Group B) and between Group A and fertile controls achieving implantation (Group C). Pre-ranked gene set enrichment (GSEA) with WebGestalt was used for pathway enrichment analysis, with Normalized Enrichment Score (NES) indicating the strength of the enrichment. Main results and the role of chance: RIF patients had a mean (± SD) age of 36.6 (± 3.4) and 5.1 ± 2.1 (mean ± SD) previous failed ETs. DGE comparisons between UF-EVs of RIF women who failed implantation (n = 10) showed 135 up- and 32 down-regulated genes compared to Group B, and 258 up- and 44 down-regulated genes compared to Group C, with 63 genes showing consistent significantly different 'expression' values in both comparisons. UF-EVs of Group A were enriched in transcripts belonging to the IL-17 pathway compared to both groups (Group A vs B, NES=2.2044, FDR <0.0001; Group A vs C, NES=2.3584, FDR <0.0001).Also transcripts belonging to the IL-10 pathway were enriched compared to both groups (Group A vs B NES=2.2741, FDR = 0.002; Group A vs C NES=2.2047, FDR < 0.0001). Among genes enriched in both DGE comparisons, C-X-C motif chemokine ligand (CXCL)1, CXCL2, CXCL8, and prostaglandin-endoperoxide synthase 2 (PTGS2) belonged to both the IL-10 and IL-17 pathway. On multivariate analysis controlling for relevant confounders (i.e. number of previous failed ETs), expression levels of CXCL8 emerged as a significant negative predictor of implantation (OR 0.675, 95%CI 0.493-0.925, p = 0.01). Limitations, reasons for caution: As the main limitation of our study, we collected UFs in the cycle immediately preceding (and not corresponding to) the euploid ET. This approach was considered the most appropriate in relation to the current paucity of data regarding the safety of UF aspiration in the same cycle of an ET. Wider implications of the findings: UF-EVs represent a source of transcriptomic markers related to the endometrial immune profile in RIF patients. Enrichment in the IL-17 and IL-10 pathways in this population could define the subgroup who is at risk for implantation failure even after euploid ET and who could potentially benefit from tailored immunotherapies. Trial registration number: not applicable